The effect of neural mobilization against sensorineural symptom reduction among hand-arm vibration syndrome survivor - Siti Ainun Marufa; Tri Noor Cahyo Widodo; Safun Rahmanto; Kurnia Putri Utami (Physical Therapy Journal of Indonesia, 2023)
Background: Hand-arm vibration syndrome (HAVS) is an occupational disease caused by exposure to vibration from work tools. Complaints often arise from sensorineural disorders that cause the arms and hands to tingle, numb, and experience decreased sensitivity. Neurodynamic mobilization is a manual therapy technique that utilizes tension and sliding movements that can reduce symptoms of sensorineural disorders. This study aims to determine the effect of neurodynamic mobilization on reducing sensorineural symptoms in patients with HAVS in welding workshop workers in Malang city. Methods: The design of this study used a pre-experimental approach with a one-group pretest-posttest design approach. There were 15 samples of welding workshop workers with symptoms of sensorineural disorders. The sample was given intervention for one month at a dose of 3x/week with one exercise consisting of 20x/set (10 slidings and ten tension) with three repetitions and a rest interval of 15 seconds/set. The assessment and evaluation instrument uses the Stockholm workshop scale. Data analysis was using the Wilcoxon test. Result: A significant decrease (p<0.000) in sensorineural symptoms among welding workshop workers in Malang city after a neurodynamic mobilization intervention was given. Conclusion: It can be concluded that providing neurodynamic mobilization decreases sensorineural symptoms of HAVS sufferers in welding workshop workers in Malang city.